2022
DOI: 10.1038/s41598-022-27333-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis predictive score around primary debulking surgery (PPSP) improves diagnostic efficacy in predicting the prognosis of ovarian cancer

Abstract: In recent years, the pretreatment inflammatory responses have proven to predict the prognosis, but no report exists analyzing the combined inflammatory response of the pre- and postsurgical treatment. The current study aims to extract the factors predicting the recurrence and create novel predictive scoring. This retrospective study was conducted at our institution between November 2006 and December 2020, with follow-up until September 2022. Demographic and clinicopathological data were collected from women wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Based on a few reports suggesting the usefulness of pretreatment peripheral WBC counts, this difference may help predict the prognosis. Our previous study showed that this difference contributes to the prognosis of ovarian cancer by comparing presurgical and postsurgical analyses [21,22]. This study rea rmed the usefulness of the differences in WBC counts in predicting recurrence.…”
Section: Discussionsupporting
confidence: 62%
“…Based on a few reports suggesting the usefulness of pretreatment peripheral WBC counts, this difference may help predict the prognosis. Our previous study showed that this difference contributes to the prognosis of ovarian cancer by comparing presurgical and postsurgical analyses [21,22]. This study rea rmed the usefulness of the differences in WBC counts in predicting recurrence.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, there have been studies on the association between tumor markers and cancer prognosis: CA125 is a prognostic tool for predicting relapse and progression of ovarian cancer; however, since CA125 is also known to be influenced by tumor histology and clinical stage, it remains controversial (33,34). Other studies have shown that pretreatment serum CA125 level is associated with disease progression of ovarian cancer (33)(34)(35). According to a previous study, serum CA19-9 levels >70.3 U/ml decrease the odds of survival in OCCC, whereas CA125 and HE4 levels do not (25).…”
Section: Discussionmentioning
confidence: 99%
“…Among several studies reported as predictive tools for PFS and OS in advanced EOC, at least to our knowledge, there is no prognostic scoring system taking into account preand post-NACT patients' data. We reported the scoring system named the prognosis predictive score around primary debulking surgery (PPSP) for progression-free survival (PFS), in which there were no patients shared in the current cohort [29]. This scoring system is effective to predict the patient's prognosis for those who underwent primary debulking surgery.…”
Section: Discussionmentioning
confidence: 99%